Development of Insulin Detemir/Insulin Aspart Cross-Reacting Antibodies Following Treatment with Insulin Detemir: 104-week Study in Children and Adolescents with Type 1 Diabetes Aged 2-16 Years - BEREKET, ABDULLAH (SPRINGER HEIDELBERG, 2016)
To study the long-term development (104 weeks) of insulin antibodies during treatment with insulin detemir (IDet) and insulin aspart (IAsp) in children with type 1 diabetes aged 2-16 years. A 52-week, two-arm, randomized trial comparing IDet and neutral protamine Hagedorn insulin, both in combination with IAsp, was followed by a one-arm, 52-week extension trial of the IDet + IAsp arm. The present analysis was conducted in children who completed the randomized trial and entered into the extension trial. Of the 177 children randomized to IDet treatment, 146 entered the extension trial. IDet-IAsp cross-reacting antibodies peaked within the first 39 weeks of treatment before gradually declining. A similar pattern was seen for IDet-specific and IAsp-specific antibodies. At end of trial (EOT), no correlation was observed between the level of IDet-specific or IAsp-specific antibodies or IDet-IAsp cross-reacting antibodies and either glycated hemoglobin (HbA1c) or basal insulin dose. Mean HbA1c was stable during the treatment period, with a slight increase over time from 8.41% (68.4 mmol/mol) at baseline to 8.74% (72 mmol/mol) at EOT. Mean IDet dose increased from 0.43 U/kg at baseline to 0.66 U/kg at EOT. Mean IAsp dose increased from 0.46 U/kg to 0.51 U/kg at EOT. Although treatment with IDet and IAsp is associated with development of specific and cross-reacting antibodies, no correlation between insulin antibodies and basal insulin dose or HbA1c was found. Novo Nordisk A/S. ClinicalTrials.gov identifiers: NCT00435019 and NCT00623194.
Keywords: Children; Clinical trial; Glycemic control; Immunity; Insulin aspart; Insulin detemir; Insulin therapy; Type 1 diabetes; NEUTRAL PROTAMINE HAGEDORN; BODY-MASS INDEX; NPH INSULIN; HYPOGLYCEMIA; RESPONSES; INFUSION